Between Revelation and Reality: Reforming Islamic Law Amidst Global Challenges - Annisa Nathania Wahyu Shabila; Aulliya Tasya Putri; Ola Fedda Mona Denona (Al-Qalam Institute, 2026)
This study aims to explore how Islamic law can adapt to contemporary global challenges while maintaining its foundational principles. The rapid advancements in technology, digital economies, and evolving social dynamics pose significant challenges to traditional Islamic jurisprudence, which often lacks the tools to address these modern concerns. By utilizing a qualitative-contextual design with a normative-philosophical approach, this research critically examines classical fiqh texts and engages with contemporary legal, social, and ethical issues. The findings reveal that Islamic law must be developed contextually through ijtihad, with a focus on the maqashid al-shariah. That usul al-fiqh must be renewed to address modern challenges. Additionally, Islamic institutions are increasingly revising curricula and issuing research-based fatwas to address issues such as fintech, gender rights, and bioethics. The integration of rational, scientific, and social considerations within the legal process highlights the importance of aligning Islamic law with modern realities. This study contributes by providing a comprehensive methodology for interpreting Islamic law in light of contemporary challenges and offers practical recommendations for future legal reforms. Future research should explore other global issues, such as AI, environmental law, and the globalization of Islamic law.